PENGEMBANGAN MANAJEMEN PERAWATAN DIRI DIABAETES MENGGUNAKAN MEDIA AUDIOVISUAL - Sri Dewi Megayanti; Sarah Kartika Wulandari (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: Complications due to diabetes can prevented if patients able to independently handle the disease properly. According several studies, there is a significant relationship between diabetes self-management (DSM) and glycemic control. Diabetes Self Management education (DSME) is the provision of health education by experienced medical personnel about the daily behavior of diabetics such as self-monitoring blood glucose (SMBG), diet, health care, monitoring of medication and physical activity. Objective: To understood the education response in DM patient using video approached. Methods: The design of this study used a Research and Development approach with a quasi-experimental research design pretest-posttest with control group. The research began with the making of a DSME educational video which was carried out in three stages : exploration, development and validation stages. After the video was produced, further testing was carried out to determine the effectiveness of the video in increasing knowledge of DM. Result: The analysis showed that after the intervention there was an increase in knowledge in the treatment group from 10% to 43.3% while in the control group from 13.3% to 23.3%. Chi square results p value 0.023 (p <0.05), there was a significant difference between the experiment group and the control group after intervention. Conclusion: The DSME through audio-visual media can be more effective in increasing knowledge of diabetes. The use of video as a learning medium would help someone get better information because used of interesting features, authentic and real language. Audio visual as a learning medium made it easier for nurses in diabetes as educators.